2008
DOI: 10.1002/adsc.200700331
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,3,4‐Trisubstituted Thiochromanes using an Organocatalytic Enantioselective Tandem Michael–Henry Reaction

Abstract: Enantioenriched 2,3,4-trisubstituted thiochromanes have been synthesized by using a cupreinecatalyzed tandem Michael addition-Henry reaction between 2-mercaptobenzaldehydes and β-nitrostyrenes. Good diastereoselectivities and enantioselectivities were obtained for the title compounds, which may be further improved through a single recrystallization (up to 98% de and> 99% ee). KeywordsHenry reaction; 2-mercaptobenzaldehyde; Michael addition; β-nitrostyrene; organocatalysis; tandem reaction Chromanes are an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(25 citation statements)
references
References 52 publications
0
24
0
1
Order By: Relevance
“…In the same year Zhao et al [70] reported an efficient synthesis of highly functionalized thiochromans having three chiral centers, using a tandem thio-Michael–Henry reaction of 2-mercaptobenzaldehydes 34 with β-nitrostyrenes 46 and using cupreine XXXIXa as catalyst in anhydrous diethyl ether. The protocol afforded the corresponding thiochroman 47 with excellent enantioselectivities and moderate diastereoselectivities (Scheme 24).…”
Section: Reviewmentioning
confidence: 99%
“…In the same year Zhao et al [70] reported an efficient synthesis of highly functionalized thiochromans having three chiral centers, using a tandem thio-Michael–Henry reaction of 2-mercaptobenzaldehydes 34 with β-nitrostyrenes 46 and using cupreine XXXIXa as catalyst in anhydrous diethyl ether. The protocol afforded the corresponding thiochroman 47 with excellent enantioselectivities and moderate diastereoselectivities (Scheme 24).…”
Section: Reviewmentioning
confidence: 99%
“…56 For example, the reaction of 2-mercaptobenzaldehyde (87) with trans -β-nitrostyrenes ( 88 ) afforded the corresponding thiochromane in 95% yield and 86% ee (Scheme 18). A series of 2-mercaptoaldehydes and nitrostyrenes with substituents of different electronic properties reacted smoothly to furnish the desired thiochromanes in moderate diastereoselectivities and good enantioselectivities (Scheme 18).…”
Section: Organocatalytic Tandem Reactionsmentioning
confidence: 99%
“…[1] As such, efficient and practical synthetic methods to establish complementary diastereoselectivity in one-pot reactions from simple materials have rarely been explored. [2] The most practical solutions to diastereodivergence from the same starting materials often rely on catalysts, especially chiral catalysts, [3][4][5][6][7] because the use of controls such as substrates, temper-ature, and solvents for complementary diastereoselectivity has been a longstanding challenge. [8] In addition, chemoselective transformations open up a new avenue for the construction of complex molecules in synthetic organic and medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%